A Research Agenda for Sustainable Consumption Governance - Mont, Oksana (Elgar Research Agendas, 2019)
Elgar Research Agendas outline the future of research in a given area. Leading scholars are given the space to explore their subject in provocative ways, and map out the potential directions of travel. They are relevant but also visionary. Evaluating achievements, challenges and future avenues for research, this book explores how new dimensions of knowledge and practice contest, reshape and advance traditional understandings of sustainable consumption governance. By questioning existing academic discourse and advocating collective solutions, up-and-coming and established scholars help readers to understand diverse governance processes through a wide variety of topics. These range from consumption impacts, the circular and sharing economy, sustainable business models, consumer behaviour and work time, to understanding the role of new actors such as prosumers and city governments. The research agenda supports transformative system changes to a more sustainable society. Policy makers at international, national and local levels will benefit from the practical advice offered and forward-thinking policy suggestions. It will also be a timely read for scholars of sustainability studies, sociology of consumption, political economy and political ecology, human geography, wellbeing, environment studies and human ecology looking to gain a more well-rounded understanding of the topic.